A dynamic key authentication protocol for RFID system. (2017) - Mu, Haibing; Zheng, Zhenlong
RFID system faces a number of security problems with its pervasive using in all kinds of fields, such as the internet of things. According to the computing and storage limitation of the tag, we propose a mutual authentication protocol based on random numbers which can help determine the new keys with their fixed key seeds. The protocol mainly applies hash function and XOR operation which can be affordable for resource-constrained tags. As to the performance of the protocol, we discuss the security as well as its storage and computation overhead. Analysis shows that our protocol can resist common attacks with good effectiveness.